Sustainable tourism and city branding: Balancing growth and authenticity - Verances, Jennifer; Rusmiatmoko, Djudjun; Afifudin, Mukhtarul Anam (Institute for Advanced Science Social, and Sustainable Future, 2024)
Background: The rapid growth of tourism has necessitated a re-evaluation of its impacts on local cultures and economies, highlighting the need for sustainable practices. This paper explores the intersection of sustainable tourism and city branding, focusing on how destinations can balance economic growth with the preservation of authenticity. Method: Through a comparative case study analysis of Indonesia and the Philippines, this research examines the strategies employed by major cities in these countries to attract tourists while maintaining cultural integrity and promoting sustainability. In Indonesia, cities like Bali and Jakarta have implemented various initiatives aimed at fostering sustainable tourism, such as community-based tourism projects and environmental conservation efforts. Similarly, destinations like Manila and Cebu have developed branding strategies in the Philippines that emphasize cultural heritage and ecological sustainability. This study identifies common challenges faced by both countries, including managing the environmental impact of tourism and ensuring local community involvement in tourism planning. Result: The findings suggest that while Indonesia and the Philippines have made significant strides in integrating sustainability into their tourism and branding efforts, substantial hurdles remain to achieving a perfect balance. Conclusion: Key recommendations include enhancing policy frameworks, increasing stakeholder collaboration, and fostering greater awareness among tourists about sustainable practices. This paper contributes to the broader discourse on sustainable tourism and city branding by providing insights that can inform policy and practice in other regions facing similar challenges. Novelty/Originality of this study: They are developing a holistic and adaptable comparative framework for evaluating sustainable tourism strategies, integrating economic, social, cultural and environmental aspects, and considering each destination's unique characteristics. Various tourism destinations can adopt and adapt this framework to develop and implement tourism practices that effectively balance economic growth, cultural preservation and environmental sustainability in their local context.